Wakif Preferences In Selecting Cash Waqf: A Case of Badan Wakaf Indonesia at Yogyakarta City - Meylianingrum, Kurniawati; Aminy, Muhammad Muhajir; Aslam, Mohd Aslam Mizan (IKONOMIKA, 2020)
Cash waqf is an Islamic financial instrument which recently is developed by most Muslim scholars. This Islamic financial instrument is believed to be one alternative to solicit social funds from people, other than zakat, with a purpose to gain sustainable benefits without reducing the amount of used fund.Cash waqf is not similar to zakat that is a mandatory and an Islamic pillar for Muslims across the world. Cash waqf is a preferable (sunnah) that is encouraged to be carried out by Muslims to gain ceaseless reward from God. Muslims who spend their money for this Islamic charity have an awareness to do more kindness as a worship form to God.This study aims to analyse the influence of four independent variables, namely religiosity, trust, service quality, and promotion factor on wakif decision to select cash waqf product in Badan Wakaf Indonesia region of Yogyakarta City. The findings showed a positive significant impact, simultaneously and partially, from all observed independent variables toward the dependent variable.Another purpose of this study is to investigate a cash waqf management that is applied in the waqf institution. The duty of Badan Wakaf Indonesia as the waqf institution is only to supervise the nazhirs, waqf managers, regarding their cash waqf management. Badan Wakaf Indonesia indirectly collects and distributes all cash waqf through all its five nazhirs.Keywords: Waqf, Cash Waqf, Wakif Preferences, Wakif Decision